Comparative analysis of animal lifespan - Nicole C. Riddle; Peggy R. Biga; Anne M. Bronikowski; James R. Walters; Gerald S. Wilkinson; Jingyue Ellie Duan; Anthony Gamble; Erica Larschan; Richard P. Meisel; Ritambhara Singh; Ashley Webb (GeroScience, 2023)
Comparative studies of aging are a promising approach to identifying general properties of and processes leading to aging. While to date, many comparative studies of aging in animals have focused on relatively narrow species groups, methodological innovations now allow for studies that include evolutionary distant species. However, comparative studies of aging across a wide range of species that have distinct life histories introduce additional challenges in experimental design. Here, we discuss these challenges, highlight the most pressing problems that need to be solved, and provide suggestions based on current approaches to successfully carry out comparative aging studies across the animal kingdom.